Edukasi Pengolahan Emas Tanpa Merkuri di Kecamatan Taludaa, Kabupaten Bone Bolango - Sukamto, Kostiawan; Lukum, Astin; Pou, Siti Nurhaliza; Abas, Dina (Universitas Negeri Gorontalo, 2024)
The activity was conducted in Taludaa Sub-district, Bone Bolango Regency, with the aim of raising awareness among miners and the surrounding community about the dangers of mercury and introducing alternative gold processing methods that are more environmentally friendly. The program included socialization through lectures, discussions, educational video screenings, and training on mercury-free gold processing methods, such as gravity techniques and controlled cyanidation. Initial surveys revealed that more than 50% of miners still relied on mercury. The results demonstrated increased participant understanding, with 80% of them recognizing the health and environmental risks posed by mercury. Practical training also highlighted the effectiveness of alternative methods, with 75% of participants expressing confidence in adopting them. Nevertheless, challenges remain in terms of equipment access and the costs of implementing new technologies. This initiative has shown a positive impact in enhancing miners' awareness and skills, serving as a significant first step toward reducing mercury use in the region and promoting sustainability in artisanal gold mining activities.